From Science to Parliament: How Empathy Became a Political Concept in Finland - Martin Pettersson (Redescriptions)
Empatia, the Finnish word for empathy, became used by politicians in Finland in the second half of the 20th century, just as other translations of the English term took root in their respective contexts. This article scrutinizes the Finnish case to find out how and why empathy became a political term there. The rise of empathy is examined in context of the growing interest in the role of political action within an immaterial realm, tracing the paths that led the concept into Finnish public discussions and contrasting it against earlier uses of sympathy. Based on this contextualization, I argue that empathy is both a symptom of the scientization of 20th-century political concepts and a continuation of a parliamentary rhetoric of positing interpersonal understanding as either important or unimportant to political decision-making. Politicians talking about empathy, while drawing on the scientific roots of the concept in psychology, still apply it rhetorically as if empathy were another word for sympathy, albeit in an improved, rational form. Parliamentary debates display how politicians use empathy to oscillate between numerous perceived dichotomies, such as nature and nurture, or individual and collective, depending on the rhetorical situation and without scientific precision. This usage highlights how scientific concepts mutate when they are made to do rhetorical work.